Efficacy of Vonoprazan for Helicobacter pylori Eradication - Kiyotoki, Shu (Intern Med, 2019)
Helicobacter pylori can infect the gastric mucosa and cause chronic inflammation, resulting in various diseases, including gastric cancer. Eradication of H. pylori in all infected subjects is recommended; however, the number of H. pylori strains with antibiotic resistance has increased, and the eradication rate has decreased. Vonoprazan, a potassium-competitive acid blocker, produces a stronger acid-inhibitory effect than proton pump inhibitors (PPIs). The H. pylori eradication rate with vonoprazan was found to be higher than that with PPIs. The H. pylori eradication rate with vonoprazan-based triple therapy (vonoprazan, amoxicillin, and clarithromycin) was approximately 90% and had an incidence of adverse events similar to that of PPIs. We review the current situation of H. pylori eradication in Japan, the first country in which vonoprazan was made available.